Brilliant glyconanocapsules for trapping of bacteria1. Issue 67 (28th August 2015) - Yan, Xibo; Sivignon, Adeline; Alcouffe, Pierre; Burdin, Béatrice; Favre-Bonté, Sabine; Bilyy, Rostyslav; Barnich, Nicolas; Fleury, Etienne; Ganachaud, François; Bernard, Julien
<x xml:space="preserve">Abstract</x> n-Heptyl α-d-mannose-functionalized nanocapsules are prepared by the Shift'N'Go process and post-modified to ensure aggregation and efficient removal of bacteria.